â€œDrug Release Kinetic Modeling and Gamma Scintigraphic Studies of Dual Ca2+ and SO4 2- Cross-linked Microbeads for Colon Specific Targetingâ€ - Lanjhiyana, S. K. (Asian Journal of Pharmaceutics (AJP), 2020)
Objectives: Ionic gelation-based polyelectrolyte complexes of blend chitosan-sodium alginate polysaccharides based microbeads of methotrexate were prepared by dual cross-linkages with divalent Ca2+ and SO4 -2 ions for colon targeting. Materials and Methods: Those developed dual cross-linked formulations were characterized for particle size, entrapment studies, drug content, swelling degree, etc. Results: The surface morphology results showed that the optimized formulations were semi-spherical and rough-surfaced. The in vitro drug release carried out in various simulated fluids at various pH had shown lesser release profiles in acidic media as compared to alkaline media at the end of 24 h studies. A significant drug release (P > 0.05) was observed in colonic fluids containing 2 and 4% w/v rat cecal as compared with control. In vivo targeting ability for the colon-specific region was established through gamma scintigraphic imaging technique. Differential scanning calorimetry and X-ray diffraction analysis further confirms for semi-crystalline and complete cross-linking state. The release profile and mathematical kinetic modeling revealed for anomalous non-Fickian type formulations were best fitted with Higuchi and Hixson-Crowell model, respectively. Conclusion: It can be concluded that the optimized formulations may be effective for colon targeting and promising to achieve drug targeting for colorectal cancer.